Trapping‐Enrichment Multi‐dimensional Liquid Chromatography with On‐Line Deuterated Solvent Exchange for Streamlined Structure Elucidation at the Microgram Scale. (21st February 2022) - Ahmad, Imad A. Haidar; Losacco, Gioacchino Luca; Shchurik, Vladimir; Wang, Xiao; Cohen, Ryan D.; Herron, Alastair N.; Aiken, Sheenagh; Fiorito, Daniele; Wang, Heather; Reibarkh, Mikhail; Nowak, Timothy; Makarov, Alexey A.; et al.
Abstract: At the forefront of chemistry and biology research, development timelines are fast‐paced and large quantities of pure targets are rarely available. Herein, we introduce a new framework, which is built upon an automated, online trapping‐enrichment multi‐dimensional liquid chromatography platform (TE‐ Dt ‐mDLC) that enables: 1) highly efficient separation of complex mixtures in a first dimension ( 1 D ‐UV); 2) automated peak trapping‐enrichment and buffer removal achieved through a sequence of H2 O and D2 O washes using an independent pump setup; and 3) a second dimension separation ( 2 D ‐UV‐MS) with fully deuterated mobile phases and fraction collection to minimize protic residues for immediate NMR analysis while bypassing tedious drying processes and minimizing analyte degradation. Diverse examples of target isolation and characterization from organic synthesis and natural product chemistry laboratories are illustrated, demonstrating recoveries above 90 % using as little as a few micrograms of material. Abstract : Trapping‐Enrichment Deuterated Multidimensional‐Liquid Chromatography (TE‐ Dt ‐mDLC) for rapid microgram‐scale structure elucidation by NMR is introduced. This concept enables a streamlined chemical characterization of multicomponent mixtures ( e.g . catalysis, natural products) while bypassing tedious drying processes with recoveries above 90 % using as little as a few micrograms of material.